Graphic-style stories to engage limited resource communities and promote health: methods for iterative co-design with community representatives - Gertz, Susan; Lee, Seung Yeon; Humphries, Jaqueline; Pettus-Ogelsby, Luwana; Martin, Lisa J.; Morris, Edith; Mabisi, Keren; Kohli, Eshika; Wilson, Kamryn L.; Beckham, Carissa; Tawwab, Vonnie; Sherman, Paula; et al. (Frontiers in Public Health, 2025)
IntroductionPeople with lower health literacy and those living in limited-resource communities often experience poorer health outcomes. Leveraging stories for health promotion can be particularly beneficial as stories are more engaging and memorable than other outreach materials. Co-designing health-promotion stories with representatives from target communities ensures their cultural relevance.MethodsWe Engage 4 Health (WE4H), a 20 + member community-academic partnership, developed an iterative co-design and testing process for creating engaging and culturally tailored health promotion stories that initiate meaningful discussions about diverse and often complex health topics. Using a graphic-style format, the stories were designed to be read aloud as the story characters together by program participants and lay educators. Herein, we share three case stories. Surveys and an online focus group gathered feedback from 17 community co-designers from a midwestern US city.ResultsOver six years, WE4H’s flexible co-design cycle facilitated the creation of over 80 stories. Topics included wellness, chronic disease, cancer, citizen science, research participation, and COVID-19/vaccines. Surveys and focus groups indicated that the co-designers felt their ideas were clearly incorporated into the final stories, which made them feel valued and more trusting of the WE4H team. Many developed a sense of ownership of the materials and were more inclined to share the finished products with their communities, strengthening the sustainability of the community-academic partnership and its related outreach programs.DiscussionWE4H’s community co-design cycle is iterative and highly transferable for creating culturally appropriate health promotion materials on diverse topics for people of varying abilities, backgrounds, and geographies.